PEMBUATAN GEL ETANOL DENGAN MENGGUNAKAN BAHAN PENGENTAL Carboxymethycellulose (CMC) - Almira Nugroho; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study is to obtain a concentration of carboxymethylcellulose (CMC) as a thickener and the appropriate concentration of ethanol in the gel formulation of ethanol as a fuel. This study was conducted experimentally by using completely randomized design (CRD) factorial. The first factor is the concentration of ethanol (70, 80 and 90%) and the second factor is the concentration of CMC (1,2, 1,5 and 1,8 grams). Results of analysis of variance showed interactions addition of ethanol concentration and concentration CMC significantly affect ethanol combustion residues gel. The addition of different concentrations of ethanol significant effect on the calorific value. The addition of different concentrations of CMC significant effect on viscosity. The heat is transferred to boil ethanol gel 100 ml of water is as much as 14,10 grams. At the beginning of the combustion flame color blue, then turn blue yellow, then yellow bluish color fire to be extinguished. The best formulations according to the characteristics of ethanol semi-solid gel that treatment E3C3 having a viscosity of 17434 cP, combustion residues 29,44%, calorific value of 11.751 J /gr. Keywords: ethanol, CMC, thickener, ethanol gel.